A BrLINE1-RUP insertion in BrCER2 alters cuticular wax biosynthesis in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Li, Biyuan; Yue, Zhichen; Ding, Xiaoya; Zhao, Yanting; Lei, Juanli; Zang, Yunxiang; Hu, Qizan; Tao, Peng (Frontiers in Plant Science, 2023)
Glossiness is an important quality-related trait of Chinese cabbage, which is a leafy vegetable crop in the family Brassicaceae. The glossy trait is caused by abnormal cuticular wax accumulation. In this study, on the basis of a bulked segregant analysis coupled with next-generation sequencing (BSA-seq) and fine-mapping, the most likely candidate gene responsible for the glossy phenotype of Chinese cabbage was identified. It was subsequently named Brcer2 because it is homologous to AtCER2 (At4g24510). A bioinformatics analysis indicated a long interspersed nuclear element 1 (LINE-1) transposable element (named BrLINE1-RUP) was inserted into the first exon of Brcer2 in HN19-G via an insertion-mediated deletion mechanism, which introduced a premature termination codon. Gene expression analysis showed that the InDel mutation of BrCER2 reduced the transcriptional expression levels of Brcer2 in HN19-G. An analysis of cuticular waxes suggested that a loss-of-function mutation to BrCER2 in Chinese cabbage leads to a severe decrease in the abundance of very-long-chain-fatty-acids (> C28), resulting in the production of a cauline leaf, inflorescence stem, flower, and pistil with a glossy phenotype. These findings imply the insertion of the LINE-1 transposable element BrLINE1-RUP into BrCER2 can modulate the waxy traits of Chinese cabbage plants.